Implementasi Strategi Direct Marketing Pada Hotel Grand Savero Bogor - Eka Nur Saputri; Ani Mekaniwati; Adil Fadillah; Sulistiono Sulistiono (Jurnal Aplikasi Bisnis Kesatuan, 2023)
ABSTRACT The development of the times causes changes, one of which is the changes that occur in the hospitality business. The high competition in hotels requires every company to be able to carry out promotions. Direct marketing is one type of promotion that can be done in order to compete in the market. The purpose of this research is to find out: 1) how to implement direct marketing at the Grand Savero Bogor hotel. 2) obstacles in carrying out direct marketing promotions at the Grand Savero Bogor hotel 3) efforts to deal with direct marketing obstacles at the Grand Savero Bogor hotel. The results of this study indicate that Hotel Grand Savero Bogor carries out direct marketing promotions by implementing several channels of direct marketing. The channels used are: 1) face-to-face sales; 2) telemarketing; 3) catalog marketing; 4) online marketing; 5) direct mail. There are obstacles in implementing direct, not being able to carry out a sales blitz in the company building if there is no appointment, marketing, namely providing information through incomplete catalogs, unstable internet connections that hinder the promotion process through telemarketing. The efforts that can be made by the Hotel Grand Savero Bogor are by making an appointment before entering the company building where you are going, as soon as possible asking for a mobile phone number to contact to avoid an unstable internet connection and preventing lost business, looking for alternative ways to send a letter of offer. i.e. via WhatsApp. Keywords : Direct Marketing, Sales Promotion, Telemarketing